Optical Studies of Poly(9,9-di-(2-ethylhexyl)-9H-fluorene-2,7-vinylene) and its Nanocomposites - Layek S.; Ghosh M.; Reddy K.S.; Senapati S.; Maiti P.; Sinha S. (My University, 2025)
Steady state and time-resolved spectroscopic measurements are carried out to understand the fluorescent optical properties of the conjugated polymer poly(9,9-di-(2-ethylhexyl)-9H-fluorene-2,7-vinylene) (PFV) in liquid phase and solid phase. Quite significant color tuning is observed in the fluorescence emission of PFV in the blue side of the spectra in the solid phase, especially in powder form, when the polymer is doped with 30B nanoclay (organically modified Montmorillonite) and graphene nanoparticles. Interestingly, the average fluorescence lifetime of PFVgraphene nanocomposite in thin film is found to be much higher (8.1 ns) compared to that for PFV only in thin film (3 ns). These novel nanocomposites may have potential applications in polymer optoelectronics industry. © 2015, Springer Science+Business Media New York.